Role of interferons (IFNs) in the differentiation of T peripheral helper (Tph) cells: 2. IFN-α and IFN-λ1 cooperatively contribute to the expansion of Tph cells in systemic lupus erythematosus. (3rd July 2022) - Tanemura, Shuhei; Seki, Noriyasu; Tsujimoto, Hideto; Saito, Shuntaro; Kikuchi, Jun; Sugahara, Kunio; Yoshimoto, Keiko; Suzuki, Katsuya; Kaneko, Yuko; Chiba, Kenji; Takeuchi, Tsutomu
Abstract: Interleukin (IL)-21-producing T peripheral helper (Tph) cells are thought to contribute to extra-follicular B cell activation and play a pathogenic role in autoimmune diseases. In this study, we investigated the relationship between Tph cells and interferons (IFNs) in several autoimmune diseases because our previous study demonstrated that type I IFNs promote the differentiation of IL-21-producing Tph-like cells. The frequency of Tph cells in the blood as well as serum IFN-α2a and IFN-λ1 were markedly elevated in patients with active systemic lupus erythematosus (SLE) compared to other autoimmune diseases or healthy controls. Notably, the frequency of Tph cells was positively correlated with the SLE disease activity index, serum IFN-α and serum IFN-λ1 in SLE patients. Additionally, we found that type III IFNs (IFN-λ1, IFN-λ2 and IFN-λ3) promote the differentiation of programmed cell death-1 (PD-1)+ CXCR5 − CD4 + T cells and enhance the secretion of IL-21, IFN-γ and CXCL13. IFN-λ1, like IFN-α, up-regulated the mRNA expression of IL21, IFNG, CXCL13, CD244, SLAMF7, GZMB, PRF1, CCR5 and PRDM1, whereas it down-regulated that of CXCR5 and BCL6, reflecting a Tph-related gene expression pattern. IFN-α in combination with IFN-λ1, IFN-λ2 or IFN-λ3 significantly increased the differentiation of PD-1 + CXCR5 − Tph-like cells and the secretion of Tph-related cytokines as compared with each IFN alone, suggesting a cooperative interaction. From these findings, it is highly probable that type III IFNs in addition to type I IFNs play a key role in the differentiation of Tph cells and that high levels of IFN-α and IFN-λ1 trigger the differentiation and expansion of Tph cells in SLE. Abstract : Co-operation of type I and type III IFNs in Tph cells in SLE Graphical Abstract: